KAJIAN SIFAT FISIKOKIMIA DAN ORGANOLEPTIK SUSU SAPI MURNI DENGAN PENAMBAHAN ASAP CAIR SELAMA PENYIMPANAN - I Ketut - Budaraga (Universitas Andalas, 2023)
This study aims to determine the effect of storage time on the quality of pure cow's milk with the addition of liquid smoke. It is also to determine the physicochemical and organoleptic properties of pure cow's milk with different storage times. The research method used was a simple Completely Randomized Design (CRD) with 5 treatment levels and 3 replications. This study used pure cow's milk and purified cocoa shell liquid smoke. The results showed that the storage time of pure cow's milk added with liquid smoke which affected pH, mass, protein content, and organoleptic. The storage time of pure cow's milk added with liquid smoke at pH ranged from 4.17 - 6.45, mass 0.96 - 1.00, protein content 4.90 - 8.50 percent, and organoleptic gave an average value of taste 5.9 - 2.2, aroma 5.3-1.9, and color 6.1-2.3.